Pembinaan Program Pengenalan dan Pelatihan Palang Merah Remaja (PMR) di SMA Al-Munawwir Sangatta Selatan - Jumrianah, Jumrianah (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This Community Service aims to assist in the implementation of the introduction and training program for the Junior Red Cross (PMR) at SMA Al-Munawwir Sangatta Selatan Islamic Boarding School. The PMR program at this school is designed to introduce students to social activities and emergency response skills, as well as build leadership and social awareness. This community service design uses a qualitative approach with the Participatory Action Research (PAR) method. The results of the implementation indicate that the introduction and training program for PMR at SMA Al-Munawwir Sangatta Selatan has been running well. This program has succeeded in providing basic knowledge about first aid, disaster management, and leadership skills to students. Most students reported an increase in emergency response skills and social awareness after participating in this program. The training also succeeded in increasing student participation in social activities and their involvement in extracurricular activities. This program identified several challenges in its implementation, including limited resources, lack of advanced training, and limited time allocated for PMR activities. Recommendations are provided to enhance the program by allocating more resources, conducting advanced training, and expanding the schedule of PMR activities to maximise their impact. This program is expected to provide insight for the development and improvement of PMR programs in other schools and support efforts to improve students' social and leadership skills through extracurricular activities